(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The conducted study revealed different results for nine tests of coordination preparedness among young gymnasts in their first year of initial training. To establish the indicators of coordination preparedness of first-year gymnasts at the initial training stage. Theoretical analysis and generalization of scientific and methodological literature data, abstraction, historical method, comparison, pedagogical testing, and methods of mathematical statistics. The pedagogical testing of young gymnasts’ coordination preparedness included: "Hunter Accuracy Test", "Romberg Test", "Ruler Catching", "10-second Foot Tapping Test", "Fine Motor Skills, Button Test", "Ball Catching on a Cone", "Shuttle Run with Ball Transfer", "Three Squats (Sit on the Floor and Stand Up) for Time", and "Climbing the Gym Wall Up and Down for Time". Involved were young gymnasts from the Ivano-Frankivsk Youth Sports School (n=130, among them: born in 2018 n=69, 2019 n=45, and 2020 n=19). One of the tests, "Ruler Catching," showed no differences among athletes of different birth years. In two other tests, "Romberg Test" and "10-second Foot Tapping Test," statistically significant differences were recorded only between gymnasts born in 2018 and 2020. The older boys showed better results, indicating the need to use these tests for assessing coordination abilities, which are closely linked to a child’s thinking processes and psychomotor skills. Analysis of variation coefficients revealed heterogeneity within subgroups and in the overall group of young gymnasts. The values of most test results did not meet normative standards, confirming significant variability within the group and subgroups by birth year. The results of the study indicate the necessity of using tests to assess coordination abilities and physical qualities in the educational and training process of first-year gymnasts, considering individual readiness indicators. This will ensure more objective evaluation and effective planning of training loads.